Challenges in Managing Myocardial Stunning Following Cardiac Arrest in a Very High-Risk NSTE-ACS Patient: A Case Report - Afandy, Jonathan Edbert; Taslim (Nusantara Medical Science Journal, 2025)
Introduction: Myocardial stunning is a reversible myocardial dysfunction that can occur due to various conditions, including focal ischemia—such as acute coronary syndrome (ACS)—and global ischemia, such as cardiac arrest. The proposed mechanisms include oxygen free radical damage during early reperfusion and altered calcium inflow leading to transient myofilament desensitization. Case Presentation: A 61-year-old woman with a history of uncontrolled hypertension and obesity presented with sudden loss of consciousness lasting one hour, preceded by chest pain and dyspnea. She experienced cardiac arrest and achieved return of spontaneous circulation (ROSC) after 10 minutes of cardiopulmonary resuscitation. Initial echocardiography showed a left ventricular ejection fraction (LVEF) of 32.9% and global hypokinesia. She was diagnosed with very high-risk non-ST-elevation ACS (NSTE-ACS), with suspected left main coronary artery obstruction or three-vessel disease. Her clinical course was complicated by acute pulmonary edema, respiratory failure, and cardiogenic shock. Management included intubation, dual antiplatelet therapy, anticoagulation, statin therapy, and inotropic support with dopamine and dobutamine. Her hemodynamic status improved within 18 hours, and she was extubated. On the third day post-arrest, follow-up echocardiography revealed a restored LVEF of 69.5% with normal wall motion. The patient was discharged after 9 days and continued to do well on outpatient follow-up for at least 6 months. Conclusions: Myocardial stunning should be considered in post-cardiac arrest and ACS patients with transient ventricular dysfunction. Early supportive care and close monitoring are essential, particularly in settings lacking advanced cardiac interventions.